ANTERIOR CROSSBITE AS A RISK FACTOR FOR THE DEVELOPMENT OF GINGIVAL RECESSION - Stilyana Krasteva (Journal of IMAB, 2018)
Introduction: A number of studies have indicated that only certain types of, such as proclined teeth, deep bite and anterior crossbite, can be considered risk factors for gingival recession. Aim: The aim of our study was to examine the association between anterior crossbite and gingival recession. Materials and methods: We monitored 80 patients aged 18 - 52 with anterior crossbite in one or more teeth. 960 teeth were examined, of which 501 exhibited gingival recession. To determine the site of the crossbite intraoral examination was utilized. We visually ascertained the presence of gingival recession and measured it with a periodontal probe CP15(UNC15). Odds ratio and chi-square test were used to examine the association between anterior crossbite and gingival recession. Results were considered statistically significant at alpha ≤ 0.05. Results: Our results show no statistically significant relationship between the presence of gingival recession and anterior crossbite in the upper jaw (p>0.05), and a statistically significant association in the lower jaw (p< 0.05). The Odd Ratio (OR) values in all lower frontal teeth were higher than 1 and statistically significant (p< 0.05). Conclusion: The risk of gingival recession development is higher in teeth with anterior crossbite in the lower jaw. In the maxilla, there is no statistically significant relationship between crossbite and gingival recession occurrence.